Research Landscape of Sustainable Development of Digital Talents in the Era of Digital Economy - Ren, Liyao; Wu, Jianxin; Wang, Yi (Journal of Educational Research and Policies, 2025)
With the rapid development of global digital technology, digital transformation has become a clear trend in the complex and uncertain development of the current global economy and society, and the sustainable development of digital talents is undoubtedly the core element promoting digital transformation. Based on the literature on digital talent research over the past decade in the Web of Science database and the basic principles and methods of bibliometrics, this paper aims to systematically outline the knowledge graph of global digital talent research and its evolution path. The findings are as follows: Research on digital talents is divided into four stages: germination, preparation, growth, and stability, which generally reflect the urgent need for digital talents in the digital economy during the digitization process, gradually shifting towards a research trend where digital talents enable the sustainable development of the digital economy. Globally, Chinese scholars attach great importance to relevant research on digital talents, with their literature accounting for the highest proportion; ‘Sustainability’ is the most cited publication on digital talent. The research community on digital talents is relatively dispersed, with most scholars in a state of “independent exploration,” and a long-term stable research community has not yet formed. Current research topics focus on three aspects: the training and development of digital talents, the application of big data and artificial intelligence technology in talent management and performance evaluation, and the skill requirements and career development paths of digital talents. For the high-quality development of the digital economy, global research on digital talents tends towards the systematic training, utilization, and management by governments, schools, and enterprises, emphasizing management talents with digital thinking and leadership, as well as the construction of digital talent training models, thereby enabling digital talents to foster the sustainable development of the digital economy.